Mystery of perinatal outcomes by COVID-19 - Das, V. K.; Pandya, Kaveri; Mathew, Bincy; Prajapati, Anjali (International Journal Of Community Medicine And Public Health, 2021)
Background: The coronavirus disease is continuously affecting the lives of all people and it has grown into a pandemic. Understanding the impact of COVID-19 on pregnancy in terms of morbidity, mortality as well as perinatal-maternal and foetal outcomes is essential to propose strategies for prevention and infection control. In this study, an attempt has been made to assess the impact of COVID-19 on perinatal outcomes. Methods: It was a retrospective analytical study. The case-files of 47 antenatal mothers who were RT-PCR positive & delivered during the course of treatment were taken for the study. Results: Out of all samples, 91.49% were asymptomatic, 10.63% had pregnancy induced hypertension (PIH) as comorbidity, 88.10% had anaemia, 40.43% had WBC count more than 10,000/mm3. 97.87 % of the samples recovered from COVID-19 with routine obstetrical management and only one case was kept on BIPAP support. Perinatal complications like preterm deliveries (27.66%), foetal distress (27.66%), NRNST (19.15%), PROM (4.26%), decreased foetal movement (2.13 %), LBW (6.38%), APGAR<7 at 5 min (15.55%), still birth (4.26%), NICU admission (31.11%), neonatal death (2.13%) were identified. 68.89% neonates were breastfed. The RT-PCR of all neonates came negative on first day of delivery which indicates that there was no vertical transmission. In this study, the results show that the perinatal outcomes are mildly affected by COVID-19. Conclusions: Although COVID-19 doesn’t directly affect perinatal outcomes, it has indirect adverse effects on MCH services. Hence, emergency obstetric and neonatal care is an essential service to be continued with awareness of people while maintaining social distancing and personal hygiene.